Using ICT and Social Media as Feedback Mechanism for Central Schemes by Beneficiaries - Bhagwat, Kanchan; Ohlan, Manisha; Shirur, Mahantesh (Journal of Agricultural Extension Management, 2022)
Diploma in Agricultural Extension Services for Input dealers (DAESI) is an important scheme which enables the input dealers to serve farmers with timely and sound advisories. After one year of rigorous training program, 90 participants from nineteen states recorded their videos and got benefited and were in a position to identify the problems in their region with respect to management of pest and diseases, doses of fertiliser’s application, with improvement in business and communication skills, and increase in self-confidence level with upgradation of knowledge. The data was assessed on a set of 12 questions in which the participants recorded their responses through videos and revealed that they were very satisfied with the one year DAESI training programme